La norma internacional de contabilidad 21 como base para la conversión de estados financieros por el método de conversión corriente. - Avila Rivera, Alexandra Soledad (My University, 2019)
Currently the expansion of international business has an accelerated growth, the benefits of technological development allow the approach of the worlds and business are not the difference, a situation that makes it necessary to have homogeneous guidelines for financial information - accounting , in response to this need, the International Financial Reporting Standards were created, which establish global standards regarding the preparation of financial information for each company, ensuring that it is of high quality and provides reliability to its users. Some companies maintain businesses outside their country of origin as a result of having gained opportunities in other markets, these entities need to consolidate their financial information, so they must convert the financial statements in foreign currency to presentation currency, being essential to know the International Standard of Accounting 21, considering that it establishes the guidelines for the application of the most feasible method to be used in the conversion. Because of the importance of knowing the guidelines of this regulation, the purpose of this research is to characterize the conversion of financial statements in foreign currency, through the correct application of IAS 21 in order to provide a practical guide to facilitate the performance of accounting professionals. Qualitative methodology was applied, which with a practical example will describe the steps to follow for a correct conversion of financial statements in foreign currency by the current conversion method supported by the provisions of IAS 21 and the compilation of scientific articles.
En la actualidad la expansión de negocios a nivel internacional tiene un acelerado crecimiento, las bondades del desarrollo tecnológico permiten el acercamiento de los mundos y los negocios no son la diferencia, situación que hace necesario contar con lineamientos homogéneos para la información de carácter financiero-contable, ante esta necesidad se crearon las Normas Internacionales de Información Financiera, que establecen estándares mundiales respecto a la preparación de la información financiera de cada empresa logrando que sea de calidad y brinde confiabilidad a sus usuarios. Algunas empresas mantienen negocios fuera de su país de origen a consecuencia de haber ganado oportunidades en otros mercados, estas entidades necesitan consolidar su información financiera, es así que deben convertir los estados financieros en moneda extranjera a moneda de presentación, siendo imprescindible conocer la Norma Internacional de Contabilidad 21, considerando que establece las pautas para la aplicación del método más factible a utilizar en la conversión. Por la importancia de saber los lineamientos de esta normativa, la finalidad de esta investigación es caracterizar la conversión de estados financieros en moneda extranjera, mediante la correcta aplicación de la NIC 21 con el fin de aportar con una guía práctica que facilite el desempeño a los profesionales contables. Se aplicó metodología cualitativa la misma que con un ejemplo práctico se describirán los pasos a seguir para una correcta conversión de estados financieros en moneda extranjera por el método de conversión corriente con el apoyo de lo expuesto en la NIC 21 y la recopilación de artículos científicos.
Keywords: CONTABILIDAD; NIIF; NIC; NIC 21